Effect of grass-based cropping systems on carbon sequestration under changing climate scenario - KUMHAR, B L; AGRAWAL, K K; RAI, H K; AHIRWAL, A; MEENA, H P; YADAV, RAJENDRA KUMAR; YADAV, B D (The Indian Journal of Agricultural Sciences, 2021)
The present investigation was conducted during two consecutive years of 2018-19 and 2019-20 entitled "Effect of grass-based cropping systems on soil health improvement in terms of carbon sequestration under changing climate scenario". Pearl millet napier hybrid sole crop was exhibited significantly higher total dry biomass 52.20 t/ha, above ground carbon 18.45 Mg/ha, below ground carbon 5.54 Mg/ha, total above and below ground carbon 23.99 Mg/ ha, above ground CO2 sequestration 67.71 Mg/ha, below ground CO2 sequestration 20.32 Mg/ha and total above and below ground CO2 sequestration 88.02 Mg/ha during experimentation. PN hybrid in paired rows + rice bean - Egyptian clover noted higher soil organic carbon stock 14.75, 12.68 and 10.03 Mg/ha, soil CO2 sequestration 54.17, 46.52 and 36.79 Mg/ha at 0-15, 15-30 and 30- 45 cm soil depth respectively, total carbon stock 57.96 Mg/ha, total CO2 sequestration 212.70 Mg/ha, and carbon credit ₹ 49264 /ha/yr over guinea grass sole crop. Among the different grass based cropping systems maximum total carbon stock and total CO2 sequestration under PN hybrid in paired rows + ricebean - Egyptian clover but pearl millet napier (PN) hybrid sole higher fodder carbon stock and fodder CO2 sequestration over guinea grass sole crop for soil health improvement under present scenario of climate change.